Dynamic single crystal to polycrystal transformation of a 1D-coordination polymer and its second harmonic generation. Issue 4 (23rd December 2015) - Cametti, Massimo; Bargigia, Ilaria; Martí-Rujas, Javier
Abstract : Single crystal to polycrystal transformation of a 1D coordination polymer upon guest release leads to a dynamic nonporous coordination polymer showing nonlinear optical properties such as second harmonic generation. Abstract : Upon guest CHCl3 release, the one-dimensional (1D) coordination polymer1 ·CHCl 3 gives rise to a non-porous structure, 1, following a unit cell volume reduction of ca. 22%. Due to the considerable structural transformation, the single crystal does not maintain its integrity, and therefore the structure determination has been carried out by combining single crystal X-ray diffraction and ab initio X-ray powder diffraction analyses. The result shows a symmetry breaking transformation leading to an acentric crystalline material (1 ), which shows nonlinear optical properties such as second harmonic generation.